Learning writing discussion skills via whatsapp using structured and unstructured discussion techniques - Pramudiyanti, Pramudiyanti; Susilo, Herawati; Marpaung, Rini Rita T. (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
The WhatsApp (WA) application is one application with very many users. Almost every student uses this application to communicate with each other about everyday conditions. As an application that is easy to use, we see an opportunity and a challenge to make this application as a learning tool together, not just a communication tool. Based on observations obtained information that all courses that take place in the Biology Education study program Academic Year 2015/2016 there are no courses that use the WA application for online discussion activities. The purpose of this study is to compare the differences between students' online discussion skills using structured discussion techniques and unstructured discussions. The study was conducted in the even semester of the 2016/2017 academic year in the Cell Biology course. The sample was 78 students. Data on student discussion skills were obtained from on-line discussion conversations for 10 meetings. Conversations are assessed using the discussion skills assessment rubric. Data were analyzed descriptively and t test statistics. Statistically the class given the structured discussion technique (mean = 56.37) was significantly different from the class given the unstructured discussion technique (Mean = 46.66), with a p value (2-tailed) 0.00 at a significance level of 0.05. The implication of the results of this study is that learning Cell Biology using the WA application is able to encourage an increase in student discussion skills, so as prospective teacher students have an awareness that